Pengembangan Peta Ramosa Materi Keragaman Sosial Budaya untuk Melatih Keterampilan Kolaborasi Siswa SD: Penelitian - Neni Amelia Nandarista; Nila Firdausy Nuzula; Muh. Arafik (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The research was conducted with the aim of developing RAMOSA Map media to train valid, practical and interesting collaboration skills. The methods used were R&D and the ADDIE model. The results of the validation of material experts scored 81.25%, from media experts 95.66%, and from users 96.61%. The average score obtained from the experts was categorized as very valid with the test decision that it can be used without revision. The practicality and attractiveness test was carried out by filling out a response questionnaire which scored 97% for practicality and 95% for attractiveness. These results are included in the very practical and interesting category with the test decision that it can be used without revision. Collaboration skills assessment was carried out through observation and scored 92%. It can be concluded that the media is able to train students' collaboration skills.